Scrutinising Nigeria’s Electoral Trajectory: The Electoral Act 2022, The 2023 Polls, and the Judiciary’s Verdict - Anjide , Solomon Timothy (Kashere Journal of Politics and International Relations, 2025)
The Consistent scheduling of elections remains a cornerstone of Nigeria’s democratic development. The 2023 general elections, marking the seventh consecutive electoral cycle since the 1999 democratic transition, significantly tested the nation’s democratic infrastructure, particularly in light of electoral reforms encapsulated in the highly anticipated Electoral Act 2022. This paper critically examines the influence of this Act on the 2023 general elections and explores the ramifications of the Presidential Election Petition Tribunal’s (PEPT) judgment for the future of elections in Nigeria. It scrutinises the deployment of technological innovations, such as the Bimodal Voter Accreditation System (BVAS) and the INEC Result Viewing Portal (IReV), for voter accreditation and results transmission, alongside the attendant operational difficulties. The analysis also highlights persistent challenges that cast doubt on the Independent National Electoral Commission’s (INEC) capacity to deliver transparent, free, and equitable elections in 2023. Employing a qualitative methodology, this study draws upon an extensive review of desktop literature, including official documents, academic books, journal articles, media reports, and legal instruments. Key findings indicate that several provisions within the Electoral Act 2022 suffer from ambiguity, with certain sections being overly broad or allowing excessive latitude for subjective interpretation. To bolster the credibility of future electoral contests, the study advocates for the safeguarding of voter interests through enhanced legal certainty across all electoral stages, necessitating the elimination of ambiguities within the Electoral Act and associated INEC guidelines. Such clarity is crucial to mitigate the risk of conflicting interpretations and foster greater public trust.